Content Validity Analyses of Qualitative Feedback on the Revised Assessment, Evaluation, and Programming System for Infants and Children (AEPS) Test - Macy, Marisa; Bricker, Diane; Dionne, Carmen; Brown, Jennifer Grisham; Johnson, JoAnn; Slentz, Kris; Waddell, Misti; Behm, Melissa; Shrestha, Heather (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Early childhood assessment practices, procedures, and tools can lay the foundation for an effective intervention program. The purpose of this article is to report the results of a content validity study conducted on a revision of Assessment, Evaluation, and Programming System for infants and children (AEPS®) Test, a widely used early childhood assessment/evaluation instrument. A panel of early childhood and early childhood special educator experts was assembled and asked to provide qualitative feedback on the content of the revised AEPS Test. Experts were asked to address five specific questions about item content, developmental sequences, and if assessment items represented quality teaching targets for young children. Qualitative results were used to modify items, developmental sequences, and area content.